Direct Torque Control of Induction Drive Using Fuzzy Controller - Lisauskas, S.; Udris, D.; Uznys, D. (Elektronika ir Elektrotechnika, 2013)
In this study the direct torque control of the induction drive with a fuzzy controller was investigated. The objective of this research was the reduction of the stator current and electromagnetic torque pulsations. The principles of the fuzzy controller development for the induction drive with a direct torque control and the obtained computer model were presented, and the simulation results were compared to the results of the induction drive under the traditional direct torque control. The implementation of the applied fuzzy controller allowed us to achieve the pulsations of the torque twice lower, the stator current, flux and the maximum overshoots were lowered. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.4366